High Dose Sesbania Grandiflora Extract Alters Rat Kidney Electrolytes based on Insights from Indonesia: Ekstrak Sesbania Grandiflora Dosis Tinggi Mengubah Elektrolit Ginjal Tikus berdasarkan Wawasan dari Indonesia - Mokhamad Amirul Hidayat; Jamilatur Rohmah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the acute toxicity of white turi flower extract (Sesbania grandiflora) on kidney electrolyte levels in rats (Rattus norvegicus). Conducted at Muhammadiyah University of Sidoarjo, male Wistar rats were divided into control and treatment groups, receiving 10,000, 15,000, and 20,000 mg/kgBW doses. Symptoms of toxicity included lethargy and hair loss, but no deaths occurred. Despite normal macroscopic kidney observations, sodium and potassium levels significantly increased with higher doses (p=0.000). These findings suggest that high doses of white turi flower extract can affect kidney electrolytes, indicating potential toxicity. Further research is needed to assess long-term safety for medicinal use. Highlights: 1. High doses increase sodium and potassium in rat kidneys.2. Symptoms: lethargy, hair loss, no fatalities.3. Requires further research for long-term safety. Keywords: Sesbania grandiflora, acute toxicity, kidney electrolytes, sodium, potassium